Some new forms of genus Corynespora from Kathmandu valley of Nepal - and H.D. BHARTIYA, MEENU, R.N. KHARWAR (Indian Phytopathology, 2002)
This paper deals with three new species of Corynespora viz., C. cucurbitaecola sp. ov. C. jasminiicola sp, novo and C. trictioides sp. novo occurring on hosts Coccinia grandis L. (Cucurbitaceae), Jasminum arborescens Roxb. (Oleaceae) and on Triumfetta rhomboidea Jacq. (Tiliaceae) respectively collected from epal during Nov.-Dec. 1993.